Association Of Diet Quality With Hba1c And Illness Perception With Cardiovascular Risk Factors In Pre-Diabetes And At-Risk Of Pre-Diabetes Subjects Visiting Pusat Sejahtera, Usm - Siddiqui, Sania (2019)
Importance of dietary modification in prevention and delay of diabetes development is fully understood in literature. However, association between diet quality and HbA1c among pre-diabetic Malaysian population remains unclear. Illness perception may have found to be vary among individuals according to their pre-diabetes status. Its association with cardio vascular disease (CVD) risk factors among pre-diabetic patients was rarely studied. This study aims to identify and compare diet quality measured by Healthy Eating Index for Malaysian adults (HEI) among study population, and to identify association between HEI and HbA1c in distinct pre-diabetes states (i.e. pre-diabetes, at-risk of pre-diabetes, undiagnosed diabetes and healthy normoglycemic) .The secondary objective of this study was to identify and compare pre-diabetes related illness perception and its association with relevant CVD risk factors among pre-diabetic and at-risk of pre-diabetic subjects. Cross-sectional study was conducted between October 2018-March 2019 at Pusat Sejahtera USM. A total of 147 participants who met desired study criteria and volunteer to participate were recruited in this study. Data on diet, illness perception, anthropometric and on biochemical profile was measured by using Food frequency questionnaire and 24-hour recall form, Malaysian Brief illness perception questionnaire (MBIPQ) and standardized methods respectively. No significant difference and association between HEI composite score and HbA1c were observed upon analysis after adjusting for confounding factors among study groups. MBIPQ dimensions such as high personal control, and disease concern was significantly associated with lower HbA1c (r = - 0.424, p = 0.039), and diastolic blood pressure (r = - 0.433, p = 0.034) among pre-diabetic subjects.